Takotsubo cardiomyopathy caused by epinephrine-treated bee sting anaphylaxis: a case report. (December 2015) - Ghanim, Diab; Adler, Zvi; Qarawani, Dahud; Kusniec, Fabio; Amir, Offer; Carasso, Shemy
Abstract Introduction Stress-induced cardiomyopathy (Takotsubo) after bee stings in patients who have received catecholamines is rare. Endogenous as well as exogenous administration of catecholamines is thought to trigger stress-induced cardiomyopathy. Case presentation A 37-year-old healthy white woman was stung by an unknown Hymenoptera that resulted in an anaphylactic reaction. Intravenous adrenaline (0.9 mg) was administered at a nearby clinic; she was transferred to our emergency room. Cardiogenic shock was diagnosed and mechanical ventilation commenced. Hemodynamic stabilization was not achieved by inotropic support and intra-aortic balloon pump insertion. Initial coronary angiography did not demonstrate any coronary obstructive lesions while her left ventricular systolic function was severely depressed. Peripheral femoral venoarterial extracorporeal membrane oxygenation was inserted as a bridge to recovery assuming possible reversible cause of the cardiogenic shock. Over the following 48 hours she was extubated and gradually weaned off venoarterial extracorporeal membrane oxygenation and inotropic support. She was discharged with a near normal left ventricular ejection fraction and in 3 weeks she was asymptomatic with normal electrocardiographic and echocardiographic examinations (left ventricular ejection fraction >65 %). Conclusions A Hymenoptera sting may be a specific cause of catecholamine cardiac depression. The presence of cardiogenic shock and its etiology should prompt aggressive management including extracorporeal membrane oxygenation as a bridge to cardiac functional recovery in such rare scenarios.